Awareness of Climate Change Impact and Adaptation in Agriculture – The Case of Albania - Zhllima Edvin; Imami Drini; Nam Jiyoung; Shoshi Pjerin; Gjika Irena (European Countryside, 2022)
The Albanian agriculture sector is deeply affected by climate change. To cope with climate change, it is necessary to understand its consequences. The views of agriculture extension service experts are crucial in improving farmers’ understanding and resilience, especially when farming practices are poorly adapted to the changing climate. This paper analyses the risks from climate change and the adaptive capacity of farmers based on an expert evaluation survey. The respondents identified prolongation of drought durations, rising temperatures, above-average occurrences of floods, pre-seasonal rainfall and frost as primary risks during recent years. Extension experts view a high (negative) impact from climate change through processes such as increased plant diseases occurrence, increased exposure to rodents, harmful insects and pests for plants and livestock, as well as forest and pasture degradation. The paper also provides experts’ opinions on the policy implications, such as considerations about adaptation strategies towards climate change.